Variasi Bahasa dalam Bahasa Gaul di Media Sosial - Azraril Azizah; Annisatul Kairiyah; Syahrul Ramadhan; Norliza Jamaluddin; Elfia Sukma (Universitas Palangka Raya, 2025)
This study aims to examine the variation of slang used by millennials and Gen-Z on social media. Slang on social media has become an important phenomenon that influences everyday communication, especially on platforms such as Instagram, TikTok, and WhatsApp. The use of slang reflects a change in the way of communicating that is more creative and informal, and functions as a means of expressing digital identity. Acronyms, neologisms, and foreign word absorptions are the main forms of language variation used. On the one hand, this phenomenon contributes to linguistic creativity that enriches the Indonesian vocabulary. However, on the other hand, excessive use of slang can have an impact on the decline in the quality of formal language, which is important in the context of education and official communication. This study uses a descriptive qualitative approach with observation techniques on various social media platforms to identify and analyze the phenomenon of slang. The results of the study show that slang becomes a symbol of social identity, strengthens relationships between individuals, and creates an inclusive digital community.